Malaysia’s Social Media and Virtual Communities: Investigating Digital Engagement, Social Problem Management, and Economic Mobility - Sarifin, Muhammad Ridhwan; Yusoff, Nur Hafizah; Muhamad Adnan, Muhamad Hariz (Makara Human Behavior Studies in Asia, 2026)
This study explores the evolving role of social media in shaping users’ digital engagement, social problem management, psychological well-being, and economic mobility in Malaysia. A total of 374 respondents participated in an online survey, selected using purposive sampling to capture active users across diverse age, income, and educational backgrounds. The study employed a structured questionnaire with Likert-scale items to evaluate perceptions of virtual community participation. Linear regression and moderation analysis were conducted to determine how social media usage predicts social issue management, emotional and social needs fulfillment, and economic opportunity access. Digital literacy was tested as a moderator between social media use and SPM. Social media had the strongest influence on psychological needs fulfillment (β = 0.52), followed by social problem management (β = 0.45) and economic mobility (β = 0.38). Digital literacy significantly moderated the relationship between social media and problem-solving capacity (β = 0.18, p < 0.05), that user competence enhances civic engagement outcomes. These results offer both theoretical and practical implications for digital inclusion strategies and community empowerment through online platforms. This study contributes to the field of digital sociology by integrating insights from social capital, uses and gratifications, self-determination, and social identity theories. It also highlights the need for inclusive platform design and policy frameworks that support both DL and EA.